Dampak Objek Wisata Religi Terhadap Pendapatan dan Peluang Usaha Masyakarat di Sekitar Makam Syekh Muhammad Arsyad Al-Banjary - Kasmah; Maulida, Sri (PPJP ULM, 2024)
This study aims to analyze the income and business opportunities of the community around the religious tourism site of Syekh Muhammad Arsyad Al-Banjari in Kelampaian Tengah Village. The research employed a descriptive method, with data collected through interviews, documentation, and questionnaires. The findings reveal that the existence of this religious tourism site has a positive impact on the local community's income. Various types of businesses, such as selling goods and services, have developed around the site, providing residents with economic opportunities to sustain their livelihoods. Tourist visits significantly create economic prospects for the surrounding community. This research is expected to provide information and insights to various stakeholders about the potential of the Syekh Muhammad Arsyad Al-Banjari religious tourism site in improving the welfare of the local population.